57.6k views
4 votes
How do i do this???????

How do i do this???????-example-1
User Eraph
by
5.2k points

1 Answer

1 vote

Answer:

2y-4-6y-12=4

-4y=20

y= -5

Explanation:

because (y+2)(y-2)=y^2-4

so we have the step to let the every part have the same denominator y^2-4

2(y-2)/(y+2)(y-2) -6(y+2)/(y-2)(y+2)=4/(y-2)(y+2)

the denominators are the same so the equality .we just need the part over be the same 2y-4-6y-12=4

y= -5

User Hexpheus
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.